Environmental challenges and sustainable future - "Bhargava, Gopal" (New Delhi, 2003)
The book studies the correlations of environment and development on a greater stance and the continuous damages covertly done to achieve the development in measures, warns the developing countries against such cruel acts, highlights the need of a wholesome environment for sustainable development. The challenges, solution-measures, views, laws and regulations etc. are discussed in length to bycott the false dichotomy of environment and development.
Keywords: Sustainable development